Cornugon (Hymenoptera: Eulophidae: Entedoninae) a new genus from tropical America including ten new species - Hansson, Christer (Zootaxa, 2011)
Cornugon gen. nov. (Hymenoptera: Eulophidae: Entedoninae) is described from the Neotropical region, including ten new species from Costa Rica, Ecuador, Honduras and Mexico: C. albicoxa, C. anais, C. bicornis, C. diabolos, C. diceros, C. gibberum, C. leios, C. petiolatum, C. reticulatum, and C. unicornis spp. nov. The monophyly of the genus is demonstrated through two putative morphological autapomorphies. One of the autapomorphies is in a recently discovered character system, wing interference colour patterns (WIPs). WIPs are used here for the first time at the generic level for the classification of insects. Cornugon is compared to Pediobius Walker with which it shares the most apomorphies.